Chemical changes in an oxisol treated with pyroligneous acid - Togoro, Aluisio Hideki [UNESP]; Santos da Silva, Juliana Aparecida dos [UNESP]; Cazetta, Jairo Osvaldo [UNESP] (Universidade Federal de Lavras (UFLA), 2014)
The use of pyroligneous acid (PA), a by-product of charcoal production, is an ancient practice applied in agriculture to control soil and plant pests and diseases. However, little is known about the chemical alterations that this product may cause on treated soil. Thus, the present work aimed to evaluate the effect of PA concentrations on soil ions movement and to verify possible soil chemical properties changes. Detachable columns were filled with Oxisol, submitted to application of 5 PA concentrations (0, 1, 2, 4, 8% v/v), followed by water infiltration in an amount corresponding to 1.5 times the soil total pore volume, and evaluated the soil of four depths (0-10, 10-20, 20-30, 30-40cm) and the leachate. The use of pyroligneous acid in concentrations up to 2 % (v/v) induces only slight decrease of k, Mg, basis saturation and total cation exchange capacity, in the 0-20 cm soil layer. The application of 4 % (v/v) and 8 % (v/v) pyroligneous acid induces severe increase on the potential acidity, and the decrease on the pH, basis saturation, total cation exchange capacity, and Ca concentration, in the layer of 0-20 cm soil. The P and K concentration reduces in the 0-20 cm soil layer by increasing from 1% to 8% the concentration of pyroligneous acid solution applied on soil surface. By increasing the PA concentration applied on the soil, there is increase of acidity, organic matter, P, K, Ca, and Mg, and decrease of sulfate in the leachate.
Keywords: Soil fertility; Leaching; Wood vinegar